OCCUPATION CHOICE IN THE AGRICULTURAL AND NON-AGRICULTURAL SECTORS BY THE RURAL YOUTH AND FEMALES IN BHUTAN - Dil Bahadur Rahut; Khondoker Abdul Mottaleb; Akhter Ali (Journal of Animal and Plant Sciences, 2017)
Using the information from the Bhutan Living Standard Surveys 2003, 2007 and 2012, and modeling occupation choice as a function of the characteristics of the sampled respondents, this study examines the agriculture and nonagricultural occupation choice in rural Bhutan, a rapidly emerging country in South Asia. Although until today the agriculture sector is the largest employer in rural Bhutan, after controlling for education and physical assets, this study shows that the rural youth and educated labor force are more inclined to work for salaries and wages rather than choosing self-employment in either the agricultural or non-agricultural sectors. Importantly, although the female labor force is in general more likely to be self-employed in the agricultural and non-agricultural sectors, the female labor force aged below 46 is less likely to be self-employed in the agricultural sector. This study demonstrates that married females in the labor force, and particularly the older females are increasingly taking over the agriculture sector from both young males and females, especially unmarried females. Policies should focus on making the agricultural sectors more attractive to the youth in Bhutan. JEL Classification: O17, O 18, D33, J24, J46
Keywords: Occupation choice; youth; female; agriculture; non-agriculture; Bhutan